"NÃo sei assim direito como Ã, eu sÃ sei que Ã AIDSâ: incentivos e barreiras ao teste de HIV/AIDS entre profissionais do sexo. - Renata Mota Rodrigues Bitu Sousa (2013)
Early diagnosis of HIV in Brazil still represents a challenge. It is estimated that about 30% of people living with HIV do not know their HIV status. 43% of the population comes to health services with late diagnosis in clinical conditions as AIDS-related. In this scenario, female sex workers - SW, are considered the most vulnerable, with HIV prevalence rate of 4.8%, while among women in the general population, the prevalence is 0.4%. Thus, the aim of this work was to understand what incentives and barriers that involve performing diagnostic testing of HIV among female sex workers in the city of Fortaleza, CearÃ. It built an analysis of their realities which tried to contribute to the reduction of vulnerabilities associated with HIV/AIDS infection. We used a qualitative approach using the methodology "Rapid Assessment" (RA) from the anthropological presuppositions. We conducted interviews with 36 SW women, field observation, and document analysis. The decision to perform an HIV test is determined by the intersection of individual, social, programmatic factors, linked to social inequalities. The disconnection between common sense and scientific knowledge, linked to the influence of religious beliefs, constituted as a barrier to testing. The prenatal was configured as a process that enables the test but does not encourage its regularity in non-pregnant time. Most respondents spoke of continued use of condom with their clients, however, do not use it with their steady partners. Women often want to do the test, however the main barrier is the difficulty of access to services. The integration of the populations most vulnerable to HIV in health care depends on the mode of organization of the health system. It is necessary to consider their demands and needs, strategically and collectively with their users.